Skin lightening practices, beliefs, and self-reported adverse effects among female health science students in Borama, Somaliland: A cross-sectional survey - Mukhtar A. Yusuf, MD; Nicma D. Mahmoud, MD; Farhan R. Rirash, MD; Benjamin K. Stoff, MD; Yuan Liu, PhD; Josette R. McMichael, MD (Wolters Kluwer, 2019)
Background: Skin-lightening (SL) products are common, especially in Africa. Adverse effects from these products represent a public health concern. Use of these products in Somaliland is unknown. Objective: This study aimed to determine the prevalence of use of SL products among female health science students, beliefs about these products and practices, and adverse effects experienced. Methods: This was a cross-sectional survey of a convenience sample of female health science students at Amoud University in Borama, Somaliland. Results: Of the 400 students who were invited to participate, 265 completed the survey (response rate: 66%). Mean participant age was 21.1 years (standard deviation: 2.0 years). The majority of students were single (91.2%) with a Fitzpatrick skin type of 3 or darker (94.2%). Past or present use of SL products was reported by 25.6% of participants, and 52.2% admitted to current use. Compared with non-users, more SL product users agreed that lighter skin color gives a woman more confidence, helps a woman have better job opportunities, and increases chances of getting married. They also agreed that advertisements on television for SL products influence a women's preference for a lighter skin tone (p < .05). More than 60% of participants were unsure what active ingredients were in their SL products. Only 9% denied any undesirable adverse effects, and the remainder reported an array of local and systemic adverse effects. The vast majority realize that SL products may cause undesirable local (92%) and systemic (89%) adverse effects. Limitations: Generalizability is limited because a nonrandomized convenience sample from one university was studied. Response bias also may have skewed results. Conclusion: Use of SL products among female health science students in Somaliland is common, and causes cutaneous and systemic adverse reactions. Use appears influenced by beliefs about the benefits of lighter skin color. Education is needed on the proper use of these products, how to avoid harmful products, and how to prevent complications. Keywords: Skin lightening, Skin bleaching, Skin whitening, Corticosteroid agents, Hydroquinone, Somaliland